2014
DOI: 10.1038/nmeth.3031
|View full text |Cite
|
Sign up to set email alerts
|

Optimized cell transplantation using adult rag2 mutant zebrafish

Abstract: Cell transplantation into adult zebrafish has lagged behind mouse due to the lack of immune compromised models. Here, we have created homozygous rag2E450fs mutant zebrafish that have reduced numbers of functional T and B cells but are viable and fecund. Mutant fish engraft zebrafish muscle, blood stem cells, and cancers. rag2E450fs mutant zebrafish are the first immune compromised zebrafish model that permits robust, long-term engraftment of multiple tissues and cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
125
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(131 citation statements)
references
References 24 publications
6
125
0
Order By: Relevance
“…The rag1 (17) and mpx (18) Histology and thymus size quantification. Thymus histology was performed as previously described (21). Briefly, 3-month-old fish were sacrificed and fixed in 4% paraformaldehyde, embedded in paraffin, and step sectioned.…”
Section: Generation Of Zap70mentioning
confidence: 99%
See 1 more Smart Citation
“…The rag1 (17) and mpx (18) Histology and thymus size quantification. Thymus histology was performed as previously described (21). Briefly, 3-month-old fish were sacrificed and fixed in 4% paraformaldehyde, embedded in paraffin, and step sectioned.…”
Section: Generation Of Zap70mentioning
confidence: 99%
“…Upon extraction, RNA was made into cDNA using SuperScript III reverse transcriptase (Invitrogen; 18080-051). tcrb and igm receptor rearrangements were PCR amplified using a nested protocol, as previously described (21). The first PCR utilized 2 ng of cDNA and was performed using an optimized 23.75-l reaction mixture with Choice Taq Blue master mix (Denville Scientific; CB4065-8).…”
Section: Generation Of Zap70mentioning
confidence: 99%
“…Because generation of mature B and T cells requires the activities of the RAG (recombination-activating gene) proteins, one way to alleviate rejection is to use mutations in the rag genes (Belizario, 2009;Tang et al, 2014;Tenente et al, 2014). As the host of transplantation we chose rag1 t26683 mutant zebrafish (hereafter rag1 mutant), which harbors a nonsense mutation in the catalytic domain of the encoded RAG1 protein resulting in loss of mature functional T and B cells (Wienholds et al, 2002;PetrieHanson et al, 2009).…”
Section: Transplantation Of a Testicular Hyperplasia Into Rag1 Mutantmentioning
confidence: 99%
“…Furthermore, Langenau et al, 15 have demonstrated that combining the coinjection approach with a heat-shock-inducible transgenic approach can induce transgene expression by heat shock in the primarily injected fish, which would be very useful in exploring the cooperative roles of oncogenes in tumor progression, as it permits gene expression to be turned on after the primary tumor is established. Very recently, Langenau and colleagues developed the first immunocompromised zebrafish model by targeting rag2 gene with engineered zinc-finger nucleases 43 . Loss of function of rag2 permitted robust and long-term engraftment of multiple tissues and cancer cells 43 , an advantage that could be useful in transplanting the heterogeneous cancer cells that overexpress candidate transgenes and assessing the effect of mosaic transgene expression on self-renewal capacity, therapeutic responses and the growth rate of these cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, Langenau and colleagues developed the first immunocompromised zebrafish model by targeting rag2 gene with engineered zinc-finger nucleases 43 . Loss of function of rag2 permitted robust and long-term engraftment of multiple tissues and cancer cells 43 , an advantage that could be useful in transplanting the heterogeneous cancer cells that overexpress candidate transgenes and assessing the effect of mosaic transgene expression on self-renewal capacity, therapeutic responses and the growth rate of these cancer cells.…”
Section: Discussionmentioning
confidence: 99%